STUDI TINGKAT LITERASI MEMBACA MAHASISWA SELAMA PEMBELAJARAN DARING - Hakim, M. Nur (Bahtera Indonesia, 2021)
Online learning activities are carried out to reduce the number of covid-19 spread and are considered quite effective to be applied by utilizing various technological media as a learning process and resource. This study aims to describe the level of reading literacy skills of students during online learning. The method used in this research is descriptive quantitative. The data collection technique is done by using a questionnaire via google form and conducting interviews to strengthen the research data. The data analysis was carried out through quantitative descriptive techniques. The data obtained from the questionnaire results are presented in the form of a percentage. Furthermore, the data is described to determine the level of students' reading literacy skills during online learning. The results showed that the reading literacy level of students during online learning was quite effective as seen from the average time spent by students in reading around 1-2 hours a day by reading subject references, using social media as a learning resource, and reading online news, because it has easy access to information via a smartphone.